2006
DOI: 10.2113/gseegeosci.12.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Hydraulic Conductivity Estimates for Intact Coal Barriers Between Closed Underground Mines

Abstract: Unmined blocks of coal, called barriers, separate and restrict horizontal leakage between adjacent bituminous coal mines. Understanding the leakage rate across such barriers is important in planning mine closure and strongly affects recharge calculations for postmining flooding. This study presents upper-limit estimates for hydraulic conductivity (K) of intact barriers in two closed mines at moderate depth (75-300 m, or 250-980 ft) in the Pittsburgh coal basin. The estimates are based on pumping rates from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Younger et al 1995;Sherwood and Younger 1997;Burke and Younger 2000;Adams and Younger 2001;Whitworth 2002;Boyaud and Therrien 2004;Winters and Capo 2004;McCoy et al 2006;Gandy and Younger 2007;Hamm et al 2008;Kortas and Younger 2007;Light and Donovan 2015). Post-audits of these applications have shown that they produce useful and realistic results, and that engineering design decisions based on their application have stood the test of time (Younger, 2004;Adams 2014).…”
Section: Existing Approachesmentioning
confidence: 99%
“…Younger et al 1995;Sherwood and Younger 1997;Burke and Younger 2000;Adams and Younger 2001;Whitworth 2002;Boyaud and Therrien 2004;Winters and Capo 2004;McCoy et al 2006;Gandy and Younger 2007;Hamm et al 2008;Kortas and Younger 2007;Light and Donovan 2015). Post-audits of these applications have shown that they produce useful and realistic results, and that engineering design decisions based on their application have stood the test of time (Younger, 2004;Adams 2014).…”
Section: Existing Approachesmentioning
confidence: 99%
“…Vertical inflow of groundwater is derived from overlying aquifers and surface water sources at shallow overburden conditions [1][2][3] but could also be associated with drainage from overmined seams in multiple seam mining scenarios. Inflow has been shown to occur as horizontal seepage across common barriers between contiguous mines [4,5] and spillage through discrete connections [6] but is typically undifferentiated. Following mine closure or sealing, dewatering pumps are typically deactivated, which leads to resaturation and filling of the abandoned mine voids.…”
Section: Introductionmentioning
confidence: 99%
“…Permeability values and gas content values for different coal groups of northern Appalachian coals can be found in published literature (Bruner, 1995). Moreover, anisotropic ratio (face cleat to butt cleat ratio) of 3.4 within the Upper Freeport coal formations has been found (McCoy et al, 2006). Adsorption studies on coal samples from nearby core holes of both the Pittsburgh coal seam and Upper Freeport coal seam were performed by Consol Energy (Winschel, 2009).…”
Section: Gas Content and Adsorption/desorption Propertiesmentioning
confidence: 99%
“…Moreover, the reservoir models also incorporate permeability anisotropy, which is common to coalbed reservoirs. A permeability anisotropy ratio of 3 has been assumed in these models based on the anisotropic values reported in the literature (McCoy et al, 2006). Cleat spacing was varied from 0.025 feet to 0.25 feet based on the published information for coal seams (Law, 1993;Steidl, 1977;Levine, 1996).…”
Section: Reservoir Modelingmentioning
confidence: 99%